A comprehensive analysis on definitions, development, and policies of nearly zero energy buildings in China. (October 2019) - Liu, Zhijian; Zhou, Qingxu; Tian, Zhiyong; He, Bao-jie; Jin, Guangya
Abstract: With the rapid development of urbanization and the improvement of living standards of residents in China, the energy consumption and carbon emissions of the building sector is expected to increase in the near future. Nearly or net zero energy buildings have become a hot topic of research to reduce the fossil energy consumption and greenhouse gas emissions in the building sector. As the largest developing country and carbon emitter around the world, China has also made significant efforts on nearly zero energy buildings in recent decades. The central government has approved many demonstration projects on nearly zero energy buildings in different climate zones for more than ten years. This paper summarizes international definitions of zero-energy buildings, analyzes the latest definition and identifies the boundaries of nearly zero energy buildings in China. It provides an overview of the current situation, detailed policies and building codes of nearly zero energy buildings in China. Suggestions were given on the development and promotion of nearly zero energy buildings in China. These findings in this paper will help to guide the government to implement more efficient and effective policies and building codes of nearly zero-energy buildings in order to reduce carbon emissions in the building sector. Highlights: The definitions of ZEB are inconsistent. Rapid development of ZEB in China is observed. The current situation of zero energy building in China is presented. The building codes and policies of ZEB from Chinese central and local governments are summarized.